Plasma intestinal alkaline phosphatase isoenzymes in neonates with bowel necrosis. - McLachlan, R (1993)
AIM--To determine if the intestinal isoenzymes of alkaline phosphatase (ALP) are biochemical markers of bowel necrosis in neonates. METHODS--Plasma ALP isoenzymes were measured in 22 babies with bowel necrosis, histologically confirmed, and in 22 matched controls. The isoenzymes were also measured in 16 infants with signs of necrotising enterocolitis, who recovered without histological confirmation of bowel necrosis. The isoenzymes were separated by polyacrylamide gel electrophoresis. Auxiliary tests for identification included neuraminidase digestion and treatment with monoclonal and polyclonal antiplacental antibodies. RESULTS--Intestinal ALP was detected in 16 infants with bowel necrosis--13 had fetal intestinal ALP (FI-ALP) and three had adult intestinal ALP (AI-ALP). FI-ALP was detected in nine of the controls. In the babies with bowel necrosis intestinal ALP was found over all gestations, but in the controls only in those less than 34 weeks. The percentages of total ALP activity due to intestinal ALP were significantly higher in those with bowel necrosis compared with matched controls (p = 0.028). In babies of all gestations diagnostic sensitivity for the presence of intestinal ALP as a marker of bowel necrosis was 73% and diagnostic specificity 59%. In babies greater than 34 weeks' gestation, diagnostic sensitivity fell to 60% but the test became completely specific. In two babies FI-ALP increased from zero/trace to high activity coincident with the episode of bowel necrosis. In 16 babies with signs of necrotising enterocolitis but unconfirmed bowel necrosis FI-ALP was detected in four. CONCLUSION--Intestinal ALP seems to be released into the circulation in some babies with bowel necrosis, but its detection does not have the diagnostic sensitivity and specificity to be a reliable biochemical marker of the condition.